2014
DOI: 10.4208/cicp.240912.180613a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Bifurcation Methods and their Application to Fluid Dynamics: Analysis beyond Simulation

Abstract: We provide an overview of current techniques and typical applications of numerical bifurcation analysis in fluid dynamical problems. Many of these problems are characterized by high-dimensional dynamical systems which undergo transitions as parameters are changed. The computation of the critical conditions associated with these transitions, popularly referred to as 'tipping points', is important for understanding the transition mechanisms. We describe the two basic classes of methods of numerical bifurcation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
174
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 116 publications
(125 reference statements)
1
174
0
Order By: Relevance
“…In practice, one has to provide the Jacobian matrix A of a deterministic fixed point and the matrix B representing the stochastic forcing in order to solve for the stationary covariance matrix C. In a matrix-based pseudo-arclength continuation method the Jacobian is available since a Newton-Raphson method is used [8]. The mass matrix M is readily available from the model equations.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, one has to provide the Jacobian matrix A of a deterministic fixed point and the matrix B representing the stochastic forcing in order to solve for the stationary covariance matrix C. In a matrix-based pseudo-arclength continuation method the Jacobian is available since a Newton-Raphson method is used [8]. The mass matrix M is readily available from the model equations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The different methods are distinguished by whether the Jacobian matrix is explicitly computed ('matrix-based' methods) or whether matrix vector products of this matrix are used ('matrix-free' methods). The applications shown in [8] range from traditional flows and free-surface flows to magneto-hydrodynamic flows and ocean flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have predominately been aimed at low-dimensional, enclosed flows, such as Taylor-Couette flow, of which a review was conducted by Cliffe et al [2001]. More recently continuation methods have been applied to larger fluid dynamics systems but with the main interest still being well-conditioned problems as the review by Dijkstra et al [2014] highlights. The studies by Wales [Wales, 2010;Wales et al, 2012b,a] have shown that continuation methods can be applied to high Reynolds number external flows, such as is of interest in this work.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] and references there. The review article [6] provides an overview of current techniques and typical applications of numerical bifurcation analysis in fluid dynamical problems.…”
Section: Introductionmentioning
confidence: 99%